Effect of Energy, Lysine and Energy/Lysine Ratio on Growth Performance Nutrient Digestibility and Serum Profile of Growing Locally Adapted Turkey - Akinsuyi M.A; Fatufe A.A. (International Journal of Biochemistry and Biomolecule Research, 2023)
This study investigated the effects of different levels of energy, lysine and energy/lysine ratios on growth performance, nutrient digestibility, and serum biochemical indices of locally adapted turkeys. The experiment lasted for 28 days. A total of one hundred and forty-four, 4-weeks old locally adapted turkey poults were completely randomized to six dietary treatments in a 2×3 factorial arrangement, replicated twice at 12 poults per replicate. Six diets were formulated. Diets 1 to 3 contained 2900 kcal/kg metabolizable energy (ME) (12.14 MJ/kg ME) while diets 4 to 6 contained 3000 kcal/kg ME (12.56 MJ/kg ME). The dietary lysine levels at the different energy levels are 13.50 g/kg, 15.00 g/kg, and 16.10 g/kg, respectively at 260 g/kg crude protein (CP) level. The resultant energy/lysine (E/Lys) ratios of diets 1 to 6 were 9:1, 8.1:1, 7.5:1, 9.3:1, 8.4:1 and 7.8:1 respectively. The daily feed intake and feed conversion ratio (FCR) of locally adapted turkeys were significantly (P<0.05) influenced by energy × lysine interaction. There was a significant (P0.05) of energy, lysine, energy/lysine ratio, and energy × lysine interaction on the final body weight (g/bird) and daily weight gain (g/bird) across all dietary treatments. There was a significant (P<0.05) effect of energy on crude fiber (%) and ether extract digestibility. There were significant (P<0.05) lysine, energy/lysine ratio, and energy × lysine interaction effects on the serum creatinine level of locally adapted turkeys in this study. Turkeys with an energy level of 3000 kcal/kg ME (12.56 MJ/kg ME), lysine level of 15.00 g/kg, and E/Lys ratio 8.4:1 had the highest final body weight (1205.40 g/bird), daily weight gain (30.05 g/bird) and feed intake (56.77 g/bird).
Keywords: Locally adapted; energy; energy/lysine ratio; lysine; nutrient requirements; poults